2020
DOI: 10.1038/s41586-020-2645-6
|View full text |Cite|
|
Sign up to set email alerts
|

PCNA activates the MutLγ endonuclease to promote meiotic crossing over

Abstract: During meiosis, crossover recombination connects homologous chromosomes to direct their accurate segregation 1 . Defects in crossing over cause infertility, miscarriage and congenital disease. Accordingly, each pair of chromosomes attains at least one crossover through processes that designate and then implement crossing over with high efficiency 2 . At the DNA level, crossing over is implemented through the formation and biased resolution of double-Holliday Junction intermediates [3][4][5] . A central tenet o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 43 publications
3
74
0
1
Order By: Relevance
“…3B), consistent with the lack of visible co-localization of Mlh3 and Msh4 foci. This Mlh3-Msh4 interaction, even transient in vivo, supports recent in vitro data showing that the activity of the human MutLγ complex is strongly stimulated by both Exo1 and MutSγ (41,42).…”
Section: Mutlγ Forms a Complex With Exo1 And Interacts With Mutsγ In Vivosupporting
confidence: 88%
“…3B), consistent with the lack of visible co-localization of Mlh3 and Msh4 foci. This Mlh3-Msh4 interaction, even transient in vivo, supports recent in vitro data showing that the activity of the human MutLγ complex is strongly stimulated by both Exo1 and MutSγ (41,42).…”
Section: Mutlγ Forms a Complex With Exo1 And Interacts With Mutsγ In Vivosupporting
confidence: 88%
“…As MSH3, but not MSH6, is required for trinucleotide repeat expansion (16), MutSβ-stimulation of MutLγ endonuclease may be integral to repeat expansion in vivo . Other protein-protein interactions have been implicated in MutLγ endonuclease activation (6365) and, interestingly, S. cerevisiae Mlh3 separation of function mutations provided evidence that distinct protein interactions may be required for MutLγ endonuclease activity in MMR and in meiosis (63, 64). Activity appears to be variably stimulated by proliferating cell nuclear antigen (PCNA) and replication factor C (RFC), depending on the assay system (47, 50, 63, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Other protein-protein interactions have been implicated in MutLγ endonuclease activation (6365) and, interestingly, S. cerevisiae Mlh3 separation of function mutations provided evidence that distinct protein interactions may be required for MutLγ endonuclease activity in MMR and in meiosis (63, 64). Activity appears to be variably stimulated by proliferating cell nuclear antigen (PCNA) and replication factor C (RFC), depending on the assay system (47, 50, 63, 65). Studies in S. cerevisiae have also indicated that Mlh3 endonuclease creates DNA breaks in the presence of RNA/DNA hybrids (R-loops) that can lead to increased instability, suggesting a link with transcription (66), though the relevance to repeat expansion in vivo is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the major CO pathway, extended D-loops are stabilized by the meiosis-specific MSH family complex MSH4-MSH5 along with other members of the functionally diverse ZMM family, including ZIP1-4, MER3, and SPO16 (reviewed in [63]). This stabilization promotes the formation of double Holliday junctions; MLH1-MLH3 is thought to be recruited to ZMM-stabilized double Holliday junctions, where it asymmetrically cleaves them into only crossover products, potentially through interactions with PCNA [64][65][66][67] (Class I COs; Figure 3A). Importantly, the Class I CO pathway exhibits interference, which results in COs that are widely and evenly spaced, as well as CO assurance, the phenomena in which each homolog pair receives at least one CO.…”
Section: Roles For Mlh1-mlh3 and Mlh1-mlh2 In Meiotic Recombinationmentioning
confidence: 99%